CLA4 regulates leaf angle through multiple hormone signaling pathways in maize. (3rd December 2020) - Dou, Dandan; Han, Shengbo; Cao, Liru; Ku, Lixia; Liu, Huafeng; Su, Huihui; Ren, Zhenzhen; Zhang, Dongling; Zeng, Haixia; Dong, Yahui; Liu, Zhixie; Zhu, Fangfang; et al.
Abstract: Leaf angle is an important agronomic trait in cereals and shares a close relationship with crop architecture and grain yield. Although it has been previously reported that ZmCLA4 can influence leaf angle, the underlying mechanism remains unclear. In this study, we used the Gal4-LexA/UAS system and transactivation analysis to demonstrate in maize ( Zea mays ) that ZmCLA4 is a transcriptional repressor that regulates leaf angle. DNA affinity purification sequencing (DAP-Seq) analysis revealed that ZmCLA4 mainly binds to promoters containing the EAR motif (CACCGGAC) as well as to two other motifs (CCGARGS and CDTCNTC) to inhibit the expression of its target genes. Further analysis of ZmCLA4 target genes indicated that ZmCLA4 functions as a hub of multiple plant hormone signaling pathways: ZmCLA4 was found to directly bind to the promoters of multiple genes including ZmARF22 and ZmIAA26 in the auxin transport pathway, ZmBZR3 in the brassinosteroid signaling pathway, two ZmWRKY genes involved in abscisic acid metabolism, ZmCYP genes ( ZmCYP75B1, ZmCYP93D1 ) related to jasmonic acid metabolism, and ZmABI3 involved in the ethylene response pathway. Overall, our work provides deep insights into the ZmCLA4 regulatory network in controlling leaf angle in maize. Abstract : ZmCLA4 is a transcriptional repressor that regulates leaf angle in maize through directly binding to its target genes, which are involved in multiple plant hormone signaling pathways.